Inflammatory mediators in nasal secretion in patients with bronchial asthma and allergic rhinitis with or without polyposis and hypertrophic sinonasal mucosa - Svetlana Viktorovna Krasilnikova; Ekaterina Ivanovna Krestova; Tatyana Ivanovna Eliseeva; Regina Niyazovna Khramova; Ksenia Viktorovna Gorbunova; Elena Alekseevna Leontieva; Dmitry Yuryevich Ovsyannikov; Natalia Anatolievna Geppe; Nailya Iskhakovna Kubysheva (Exploration of Medicine)
Aim: The pathogenetic mechanisms and predictors of the development of polyposis and hypertrophy of the sinonasal mucosa (SM) in patients with chronic allergic airway inflammation have not been clearly established. The concentration of inflammatory biomarkers in nasal secretions was determined in children and adolescents with a combined course of bronchial asthma (BA) and allergic rhinitis (AR) in the absence or presence of polyposis and hypertrophy of the SM. Methods: A single-centre observational cross-sectional pilot study was conducted. 93 patients with BA aged 8 to 17 years were studied. Total Nasal Symptom Score (TNSS), sinonasal symptoms (SNOT-22), and peak nasal inspiratory flow (PNIF) were assessed. Concentrations of eosinophil cationic protein (ECP), interleukin 4 (IL-4), IL-1, total immunoglobulin E (IgE), and vascular endothelial growth factor (VEGF) in nasal secretions were determined. Results: The levels of ECP, IL-4, and IL-1 in nasal secretions were statistically significantly higher in patients with the presence of polyposis and hypertrophic SM than in those without, amounting to 83.1 [31.4; 166.8] ng/mL for ECP vs. 29.5 [5.3; 49.9] ng/mL, P < 0.001, for IL-4 174.6 [68.6; 325.5] pg/mL vs. 79.5 [42.8; 146.01] pg/mL, P = 0.004, for IL-1 98.7 [33.7; 267.5] pg/mL and 48.8 [9.01; 108.2] pg/mL, P = 0.025. There were no statistically significant differences in IgE and VEGF levels in nasal secretions, all P > 0.05. Parameters such as ECP, IL-4, and IL-1 were found to be significant predictors of polyposis and hypertrophy in the formation of SM. Conclusions: In patients with a combined course of BA and AR, the presence of polyposis and hypertrophy of SM is associated with higher levels of ECP, IL-4, and IL-1 in nasal secretion. This may indicate that pathological remodelling of SM is associated with both the intensity of allergic inflammation and its relationship with local activation of innate immunity.